2021
DOI: 10.1108/ijcma-04-2021-0064
|View full text |Cite
|
Sign up to set email alerts
|

Work–family conflict, family well-being and organizational citizenship behavior: a moderated mediation model

Abstract: Purpose This study aims to examine the consequences of work–family conflict and explore the mechanism by which it influences organizational citizenship behavior from the perspective of changes in and preservation of family well-being (emotional resources). Design/methodology/approach Work–family conflict has always been an important research topic in the field of organizational behavior; scholars have studied the relationship between it and organizational citizenship behavior from different perspectives. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…First, this study makes a significant addition to the limited research on the understanding of WFC and SEB with EI as a mediator and OI as a moderator. Notably, WFC has been extensively researched (such as Lin et al , 2022; Nauman et al , 2020; Pradhan and Gupta, 2021; Yu et al , 2020), an absolute dearth of studies examining WFC and SEB relationship was found as this association has not garnered attention, thereby making our study unique and novel.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study makes a significant addition to the limited research on the understanding of WFC and SEB with EI as a mediator and OI as a moderator. Notably, WFC has been extensively researched (such as Lin et al , 2022; Nauman et al , 2020; Pradhan and Gupta, 2021; Yu et al , 2020), an absolute dearth of studies examining WFC and SEB relationship was found as this association has not garnered attention, thereby making our study unique and novel.…”
Section: Discussionmentioning
confidence: 99%
“…Control Variables. We controlled for employee demographic information, such as gender (male or female), age (in years) and job tenure (in months), since age has been found to be associated with OCB [ 80 ], and gender and job tenure have been found to be associated with customer satisfaction [ 81 , 82 ]. The data were collected through the survey questionnaire and were double-checked with the archival data provided by HR.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers might consider conducting longitudinal designs or more complex research designs to facilitate more casual evaluations for future studies. Second, the traditional methods used in this study are mainly derived from Western cultural traditions, while the connotation of work-family conflict with distinct Chinese cultural backgrounds is different in the West ( Wang and Peng, 2017 ; Lin et al, 2021 ). The development and application of more fitting scales based on the Chinese context is needed.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Family support ensures the emotional stability of female employees and further enhances their happiness ( Cates et al, 2010 ). Literature reviews reveal that philosophers and psychologists have identified happiness (or, more broadly, subjective well-being) as one of the essential characteristics of a good life and a good society ( Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%